2021
DOI: 10.3390/cancers13071585
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations of Chromosomes 1 and 16 in Breast Cancer: A Framework for Cooperation of Transcriptionally Dysregulated Genes

Abstract: Derivative chromosome der(1;16), isochromosome 1q, and deleted 16q—producing arm-level 1q-gain and/or 16q-loss—are recurrent cytogenetic abnormalities in breast cancer, but their exact role in determining the malignant phenotype is still largely unknown. We exploited The Cancer Genome Atlas (TCGA) data to generate and analyze groups of breast invasive carcinomas, called 1,16-chromogroups, that are characterized by a pattern of arm-level somatic copy number aberrations congruent with known cytogenetic aberratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 99 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…Also similar to our data, co-occurrence of 1q-gain and 16q-loss is a frequent cytogenetic abnormality in breast cancer. Transcriptome and functional pathway analysis suggested cooperation of overexpressed 1q genes and underexpressed 16q genes in the genesis of both ductal and lobular carcinomas (45). These data support our findings of 1q, 8q, 11q, 16q and 17p alterations to be present in all samples including the primary tumour.…”
Section: Discussionsupporting
confidence: 89%
“…Also similar to our data, co-occurrence of 1q-gain and 16q-loss is a frequent cytogenetic abnormality in breast cancer. Transcriptome and functional pathway analysis suggested cooperation of overexpressed 1q genes and underexpressed 16q genes in the genesis of both ductal and lobular carcinomas (45). These data support our findings of 1q, 8q, 11q, 16q and 17p alterations to be present in all samples including the primary tumour.…”
Section: Discussionsupporting
confidence: 89%
“…These clones expanded over time and acquired additional mutations that eventually led to cancer development 32 ( Supplementary Figure 8 ). While 1q/16q CNAs were found to be the only CNAs for some low grade tumors, these alterations are also associated with high aneuploid tumors 38 . Due to limitations in the resolution of our sequencing data, we were unable to confirm whether 1q-gain/16q-loss clones in our dataset were a result of der(1;16).…”
Section: Discussionmentioning
confidence: 96%
“…Fukumoto et al, found that m 6 A modification on FZD10 mRNA is correlated with the PARPi resistance via Wnt/β-catenin pathway [153]. Interestingly, PARP1 and Wnt/β-catenin pathways were found to be enriched in BRCA bearing the specific chromosomal aberrations (Chr1q gains and Chr16q losses) [154]. More studies are needed to investigate the possibility of methyladenosine modification modulating therapeutic resistance by regulating aberrations of chromosomes in cancers.…”
Section: Modulating Therapeutic Resistance and Self-renewal Of Cancersmentioning
confidence: 99%